The age, height, and body mass of Olympic swimmers: A 50-year review and update - Mallett, A.; Bellinger, P.; Derave, W.; Osborne, M.; Minahan, C. (International Journal of Sports Science & Coaching, 2021)
A difficulty in identifying the optimal age, height, and body mass of swimmers is the heterogeneity of the athletes examined (i.e., gender, caliber), the variability in race distance and stroke, and the influence of time. Nonetheless, age, height, and body mass remains the most readily available data of all athlete characteristics, supporting their contribution to the prediction of performance. This review presents the findings of previous studies over the last 50 years and offers new insights by examining data from swimmers competing at the 1968, 1992, and 2016 Olympic Games. Our data investigates gender differences in age, before exploring gender-specific variations in the age, height, and body mass across year, distance, stroke, and caliber. We show that there are differences in swimmers competing at the 2016 compared to the 1968 and 1992 Olympic Games. Today the age of world-class swimmers is independent of gender, race distance and stroke, as well as caliber. Swimmers competing in freestyle are taller and heavier than in butterfly, while height remains associated with performance in some, but not all events in female swimmers. In 2016 the average age, height and body mass of World-class swimmers is 22.7 ± 3.6 and 23.2 ± 23.3 years, 175.1 ± 6.6 cm and 188.3 ± 6.0 cm and 63.8 ± 6.8 and 81.3 ± 7.3 kg for females and males respectively. These findings provide coaches with a new perspective on the optimal age, height, and body mass of world-class female and male swimmers.